2019
DOI: 10.1002/cpe.5137
|View full text |Cite
|
Sign up to set email alerts
|

A modified hybrid whale optimization algorithm for the scheduling problem in multimedia data objects

Abstract: SummaryThe scheduling of the Multimedia Data Objects (MDO) is a difficult and extraordinary issue that faces us in the World Wide Web (WWW) to minimize the response time for clients to finish rapidly their tasks. MDO scheduling problem can be modeled as a Two‐Machine Flow Shop Scheduling Problem (T‐MFSSP) that minimizes the makespan. Notwithstanding another objective is to decrease the average lateness time of the clients' jobs. This paper proposes a Modified Hybrid Whale Algorithm (MHWA) to solve a standout a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Abdel‐Basset et al [ 157 ] proposed a modified hybrid whale optimization algorithm (MHWA) for the scheduling problem in multimedia data objects. The solutions' quality is improved by repeatedly applying mutation and reverse block insertion operations.…”
Section: Improved Woa Variantsmentioning
confidence: 99%
“…Abdel‐Basset et al [ 157 ] proposed a modified hybrid whale optimization algorithm (MHWA) for the scheduling problem in multimedia data objects. The solutions' quality is improved by repeatedly applying mutation and reverse block insertion operations.…”
Section: Improved Woa Variantsmentioning
confidence: 99%
“…It has been observed that this exploration is accomplished by generating index bubbles along a circle or paths. [41][42][43] The WOA algorithm is one of the nature-inspired optimization algorithms which is inspired from the bubble net hunting process of the humpback whales and can be used in different optimization problems. [44][45][46] The algorithm starts with a random vector of variables as the whale's population to find the global solution for the optimization problem.…”
Section: The Original Waomentioning
confidence: 99%
“…Humpback whales prefer to hunt bunches of small creatures or fish near the water's surface. It has been observed that this exploration is accomplished by generating index bubbles along a circle or paths …”
Section: Wao Based On Chaos Theorymentioning
confidence: 99%
“…These applications not only have large amount of data, but also have higher requirements for real‐time processing, which also put forward higher requirements for cloud computing or data center management 7‐9 . In particular, the scheduling system should meet the needs of all kinds of application tasks, such as real‐time, 10 reliability, 11 security, 12 energy consumption, 13 and so on.…”
Section: Introductionmentioning
confidence: 99%